Psychological treatment of reported sleep disorder in adults with intellectual disability using a multiple baseline design. - Gunning, M; Espie, C (2003)
BACKGROUND: The literature on sleep disturbance in adults with intellectual disability (ID) is sparse. Although prevalence rates for sleep disorders appear similar to those of non-disabled populations, previous treatment studies have largely been comprised of uncontrolled cases. Therefore, the present study adopted a single-case experimental methodology to evaluate behavioural sleep intervention. METHODS: A screening questionnaire was posted to 384 adults with ID and the sleep pattern of respondents with possible sleep disorders was further assessed using a structured diagnostic schedule. From the sleep-disordered subgroup, 12 participants were selected for a 4-week behavioural sleep intervention that was evaluated using randomly allocated, multiple-baseline, across-subjects designs and within-subject interrupted time series analyses (ITSAs). RESULTS: A total of 155 adults with ID (83 females and 72 males; mean age = 32 years, SD = 16.5 years), or their carers, completed the questionnaire (return rate = 40%). The application of sleep diagnostic criteria revealed that 17% had clinically significant difficulty getting to sleep and 11% had difficulty remaining asleep. Nine out of the 12 participants recruited for the intervention completed all the experimental phases, thus providing three sets of three multiple-baseline designs. Visual inspection of within- and between-subject effects suggested beneficial treatment-specific effects across a range of target variables. The ITSA confirmed significant effects (P < 0.05) or trends (P < 0.10) for six out of the nine participants. CONCLUSIONS: Behavioural sleep management may improve sleep pattern or sleep-related functioning in the majority of adults with ID who have significant sleep problems. The single-case methodology is helpful in addressing the heterogeneity of individual presentation, although clinical trial methodology is required to confirm these findings on a larger scale.